DIMENSI KRITIS PEMIKIRAN AKUNTANSI YANG TERALIENASI: DIALOG IMAJINER KONSTRUKSIONIS DAN DEKONSTRUKSIONIS - Akhmad Riduwan; Andayani Andayani (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2019)
This article aims to: (1) elevate the critical dimension of accounting thoughts which is alienated and repressed by dominant mainstream thought; and (2) build awareness of accounting academics and practitioners that (a) financial accounting can not only be developed by reflecting on economic and financial theories but can also be developed by reflecting on critical theories of sociology; and (b) accountants are not